Domestic dog demographics and estimates of canine vaccination coverage in a rural area of Zambia for the elimination of rabies - Kaneko, Chiho; Omori, Ryosuke; Sasaki, Michihito; Kataoka-Nakamura, Chikako; Simulundu, Edgar; Muleya, Walter; Moonga, Ladslav; Ndebe, Joseph; Hang’ombe, Bernard M.; Dautu, George; Qiu, Yongjin; Nakao, Ryo; et al. (PLOS Neglected Tropical Diseases, 2021)
An estimated 75% or more of the human rabies cases in Africa occur in rural settings, which underscores the importance of rabies control in these areas. Understanding dog demographics can help design strategies for rabies control and plan and conduct canine mass vaccination campaigns effectively in African countries. A cross-sectional survey was conducted to investigate domestic dog demographics in Kalambabakali, in the rural Mazabuka District of Zambia. The population of ownerless dogs and the total achievable vaccination coverage among the total dog population was estimated using the capture-recapture-based Bayesian model by conducting a canine mass vaccination campaign. This study revealed that 29% of the domestic dog population was under one year old, and 57.7% of those were under three months old and thus were not eligible for the canine rabies vaccination in Zambia. The population growth was estimated at 15% per annum based on the cross-sectional household survey. The population of ownerless dogs was estimated to be small, with an ownerless-to-owned-dog ratio of 0.01-0.06 in the target zones. The achieved overall vaccination coverage from the first mass vaccination was estimated 19.8-51.6%. This low coverage was principally attributed to the owners' lack of information, unavailability, and dog-handling difficulties. The follow-up mass vaccination campaign achieved an overall coverage of 54.8-76.2%. This paper indicates the potential for controlling canine rabies through mass vaccination in rural Zambia. Rabies education and responsible dog ownership are required to achieve high and sustainable vaccination coverage. Our findings also propose including puppies below three months old in the target population for rabies vaccination and emphasize that securing an annual enforcement of canine mass vaccination that reaches 70% coverage in the dog population is necessary to maintain protective herd immunity.